Individual difference in β-band corticomuscular coherence and its relation to force steadiness during isometric voluntary ankle dorsiflexion in healthy humans. Issue 2 (February 2017) - Ushiyama, Junichi; Yamada, Junya; Liu, Meigen; Ushiba, Junichi
Highlights: Corticomuscular coherence (CMC) was estimated during isometric ankle dorsiflexion. Magnitude of β-band CMC was widely varied across healthy individuals and correlated positively with amount of force fluctuation. CMC may determine one's ability to stabilize muscle force output. Abstract: Objective: Magnitude of β-band coherent neural activities between the sensorimotor cortex and contracting muscle is known to vary across healthy individuals. To clarify how this variance affects actual motor function, this study examined associations between the corticomuscular coherence (CMC) and force steadiness. Methods: CMC was calculated between scalp electroencephalograms (EEGs) over the sensorimotor cortex and surface electromyograms (EMGs) from the tibialis anterior muscle during tonic isometric voluntary ankle dorsiflexion at 30% of maximal effort in 22 healthy individuals. We calculated the maximal peak of CMC (CMCmax), and examined its relations to some measures of force fluctuation, such as the coefficient of variation (ForceCV), the sum of the power spectral density within 1–4 Hz (Forceδ-PSD), 5–14 Hz (Forceα-PSD), and 15–35 Hz (Forceβ-PSD) bands of force signal. Results: In all participants showing significant CMC, CMCmax was observed within the β-band. CMCmax was varied across participants (range, 0.084–0.451), and was correlated significantly and positively with ForceCV ( r  = 0.602, p  = 0.003), Forceβ-PSD ( r  = 0.637, p  = 0.001), Forceα-PSD ( r  = 0.647, p  = 0.001), and Forceδ-PSD ( r  = 0.518, p  = 0.014). Conclusion: The magnitude of the CMC between EEG over the sensorimotor cortex and EMG of contracting muscle is associated with the amount of force fluctuation during tonic isometric voluntary ankle dorsiflexion in healthy humans. Significance: CMC may influence an individual's ability to stabilize their muscle force output.